Enhancing Speaking Performance and Reducing Speaking Anxiety Using Ted Talks - Nurfitriani Arifin; Mursalim Mursalim; Sahlan Sahlan (Halu Oleo University, 2020)
This study aims at (1) investigating the effect of TED Talks on students speaking performance; (2) investigating whether or not gender affects speaking performance; (3) investigating the effect of TED Talks on reducing speaking anxiety; and (4) identifying whether or not gender affects anxiety. The study involved 42 students as the sample from 217 tenth graders of SMA Negeri 8 Kendari. The students were grouped into 2 cohorts, experimental and control class. Under quasi-experimental design, the students were assessed on their speaking performance and language anxiety. The data were analyzed using independent sample t-test and paired sample t-test using SPSS 20.0. The result of the study revealed that (1) TED Talks had a significant effect on improving student speaking performance; (2) prior to any treatment, there was no significant difference between male and female students on their speaking performance; (3) TED Talks was proven to have a significant effect on reducing student speaking anxiety; and (4) gender was not proven to have a significant effect on language anxiety. Implications of the study will be critically examined in this paperKeywords: TED Talks; Speaking Performance; and Anxiety